Analisa Kesuksesan Sistem Informasi E-Rapor Menggunakan Model Delone Mclean Dan Acceptance Technology Model (TAM) - Rusandy, Deby Santyo (Universitas Islam Kadiri, 2024)
This study aims to determine the effect of service quality, system quality, information quality, and perceived usefulness on user satisfaction of e-Rapor information systems at SMAN 1 Gondanglegi, in addition to finding which variables have the most dominant influence. The analysis technique in this study uses the DeLone Mclean model (2003) and the Acceptance Technology Model (TAM) (2003). The object of this research is the e-Report information system with the subject being teachers and staff. The number of samples used as many as 49 people. Data collection techniques using a questionnaire. Test the validity with the product moment method. To test the reliability using the alpha formula. And for regression testing, the assumption test method and significance model testing were used, using SPSS version 26 software. The results of this study that all the results of the questionnaire are valid and reliable. For the relationship of variables depending on each variable, namely, service quality and information quality have a positive and significant influence on user satisfaction. System quality and perceived usefulness have a negative and partially insignificant effect on user satisfaction. The variable that has the most dominant influence on user satisfaction is service quality.